Up-to-date criminal reference, 2000-2005 (Dhaka : Bangladesh Law Chronicles, 2006)
Reference work of Bangladesh Law Chronicles.
Keywords: Criminal procedure -- Bangladesh -- Digests; Criminal law -- Bangladesh -- Digests